A method for purifying new pollutants in water by using high-valent manganese ions and synergistic active agents
Through the method of high-valent manganese ion synergistic active agent, combined with nanofiltration, ozone and hydrogen peroxide, sea anemone-like MXene composite material containing high-valent manganese ions is used to solve the problem of difficult removal of new pollutants in the water, and achieve an efficient and environmentally friendly sewage purification effect.
Patent Information
- Application Number
- CN202411419227.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The prior art is difficult to effectively remove new pollutants in the water, such as environmental endocrine disruptors, drug residues and microplastics, making it difficult to control environmental and health risks.
The purification rate of new pollutants in water is improved by nanofiltration treatment, coordinated treatment of ozone and hydrogen peroxide, and the use of anemone-like MXene composite materials containing high-valent manganese ions.
It significantly improves the purification rate of new pollutants in the water, enhances the removal capacity of difficult-to-degrade organic matter, reduces the cost of sewage treatment, and reduces the risk of secondary pollution, making it more environmentally friendly.
Smart Images

Figure CN118993448B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, and in particular to a method for purifying new pollutants in water by using high-valent manganese ions in conjunction with an active agent. Background Art
[0002] Contaminants of Emerging Concern (CECs) refer to chemical substances that are environmentally persistent, bioaccumulative and biotoxic. The environmental and health risks of these substances are relatively hidden, and even if they enter the environment at low doses, they may pose risks and hidden dangers to our physical health, environmental health and environmental safety.
[0003] The types of new pollutants mainly include: environmental endocrine disruptors (EDCs), pharmaceuticals and personal care products (PPCPs), nanomaterials (NMs), perfluorinated organic compounds (PFCs), brominated flame retardants (BFRs) and antibiotic resistance genes (ARmg), etc., which have been detected in water supply, sewage, sludge anaerobic digestion systems, estuaries and coastal areas. Although the concentration in the environment is low (usually μg / L~ng / L), it will have a great negative impact on ecology and human health, including the increase in the number and types of drug-resistant microorganisms, interference with the reproductive development and hormone synthesis of organisms, damage to the immune system of animals and carcinogenic risks.
[0004] In order to solve the above problems, the present invention decides to design a method for purifying new pollutants in water by using high-valent manganese ions in collaboration with an active agent to further improve the purification rate of new pollutants in water. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for purifying new pollutants in water by using high-valent manganese ions in conjunction with an active agent.
[0006] A method for purifying new pollutants in water using a high-valent manganese ion synergistic active agent comprises the following steps:
[0007] S1. Perform nanofiltration treatment on the sewage at a temperature of 25-35°C and a pressure of 15-25 bar to obtain filtered water;
[0008] S2. At 20-25°C, add the active agent to the filtered water at a solid-liquid ratio of 1L:20-40mg, and introduce ozone with a volume concentration of 2.5-3.5% into the filtered water at a ventilation rate of 1-2L / min for 15-20min.
[0009] Then the temperature is raised to 40-60°C, and the active agent and the composite material containing high-valent manganese ions are added according to the solid-liquid ratio of 1L:5mg:10-15mg. Hydrogen peroxide with a volume concentration of 5-8% is introduced into the filtered water at a ventilation rate of 0.2-0.5L / min for 5-10 minutes.
[0010] The temperature is then raised to 70-80° C., a composite material containing high-valent manganese ions is added separately at a solid-liquid ratio of 1 L:2-5 mg, and ozone with a volume concentration of 5-6% is introduced into the filtered water at a ventilation rate of 6-8 L / min for 5-10 minutes to obtain purified water;
[0011] S3. The purified water is subjected to reverse osmosis treatment at a temperature of 25 to 35° C. and a pressure of 15 to 25 bar to complete the purification.
[0012] Furthermore, the preparation method of the composite material containing high-valent manganese ions is:
[0013] The anemone-shaped MXene nanomaterial is stirred and mixed in a mixed solution at a solid-liquid ratio of 0.2 to 0.3 g: 1 L for 4 to 5 hours, wherein the mixed solution is prepared by mixing a 0.2 to 0.3 mol / L potassium permanganate solution and a 0.7 to 0.9 mol / L manganese sulfate solution at a molar ratio of 1 to 1.5:1 to obtain a composite nanomaterial;
[0014] After washing and drying the composite nano material, the composite nano material is thermally oxidized at 200-300° C. for 30-40 minutes to obtain a composite material containing high-valent manganese ions.
[0015] Description: MXene material itself has a high specific surface area and good conductivity. Combined with the oxidation ability of high-valent manganese ions, it can effectively adsorb and degrade new pollutants in sewage, such as endocrine disruptors, drug residues and microplastics. The presence of high-valent manganese ions significantly enhances the oxidation ability of the material, which can accelerate the oxidation and decomposition of new pollutants and improve treatment efficiency. Thermal oxidation treatment not only improves the chemical stability of the composite material, but also may promote the recycling of materials and reduce the cost of sewage treatment. The composite nanomaterials prepared by this method are easy to handle after sewage treatment, reducing the risk of secondary pollution and being more environmentally friendly.
[0016] Furthermore, the preparation method of the anemone-like MXene nanomaterial is:
[0017] Using a MAX phase bulk material as a working electrode, AgCl as a reference electrode, and platinum as a counter electrode, the working electrode, the reference electrode, and the counter electrode are immersed in an electrolyte at a voltage of 5 to 30 V, and electrochemically stripped for 4 to 6 hours, and then centrifuged, washed, and dried to obtain MXene nanorods; wherein the electrolyte is a mixed solution of acetone and lithium perchlorate, and the concentration of lithium perchlorate in the mixed solution is 0.1 to 0.2 mol / L;
[0018] Add MAX phase precursor powder with a particle size of 500-600 nm into deionized water to form a suspension, transfer the suspension to a hydrothermal reactor, heat at 140-160°C for 8-12 hours, and then centrifuge, wash and dry to obtain MXene nanowires;
[0019] The prepared MXene nanorods and MXene nanowires were mixed and dissolved in a dimethyl sulfoxide solution at a mass ratio of 1:5-10, mixed for 3-4 hours, and then centrifuged, washed, and dried to obtain anemone-shaped MXene nanomaterials.
[0020] Description: MXene nanorods and nanowires have a large specific surface area, which increases their contact opportunities with pollutants and improves adsorption and catalytic efficiency. The MXene nanostructure formed during the electrochemical stripping process usually has good chemical stability, which helps to maintain the performance of the material during sewage treatment. The anemone-like composite material obtained by combining the two has a unique three-dimensional structure, which provides a large number of active sites, can effectively adsorb new pollutants in the water, and can be highly combined with manganese ions, thereby improving the stability of manganese ions, which in turn helps to maintain the structure and performance of the composite material containing high-valent manganese ions during sewage treatment, thereby improving the treatment efficiency and the reusability of the material.
[0021] Furthermore, the aspect ratio of the MXene nanorods is 6-9, and the aspect ratio of the MXene nanowires is 20-25.
[0022] Note: If the aspect ratio of nanorods and nanowires is too small, the application activity of the nanomaterials will be limited, while if the aspect ratio is too large, it will easily lead to agglomeration and other phenomena, affecting the effect and degree of binding.
[0023] Furthermore, the MAX phase material is Ti3SiC2, and the MAX phase precursor powder is Ti3AlC2.
[0024] Description: The above materials have excellent properties such as high temperature resistance, oxidation resistance, high strength and corrosion resistance.
[0025] Furthermore, in step S1, the pore size of the nanofiltration membrane is 1-2 nm; in step S3, the pore size of the reverse osmosis membrane is 0.0005-0.0008 μm.
[0026] Note: The filter diameters of the above two membranes can first screen out larger pollutants and then remove smaller sediments, achieving a good filtering effect.
[0027] Furthermore, the active agent is sodium bisulfite.
[0028] Description: Sodium bisulfite can effectively reduce high-valent metal ions in water, such as hexavalent chromium (Cr(VI)) to trivalent chromium (Cr(III)), thereby reducing the toxicity and mobility of these metal ions. Through the reduction reaction, sodium bisulfite helps to convert dissolved metal ions into insoluble hydroxide precipitates, which is convenient for subsequent physical separation. Sodium bisulfite has little environmental impact, and its decomposition products are relatively harmless, which helps to reduce secondary pollution.
[0029] Furthermore, the new pollutants are one or more of EDCs, PPCPs, NMs, PFCs, BFRs, and ARmg.
[0030] Note: High-valent manganese ion synergistic active agents can degrade the above-mentioned new pollutants ultra-fast within milliseconds.
[0031] Compared with the existing method for purifying new pollutants in water, the beneficial effects of the present invention are:
[0032] (1) The purification method of the present invention first performs nanofiltration treatment on the sewage to effectively remove suspended solids, colloids and some organic matter in the water, providing cleaner water quality for subsequent treatment; then the active agent is synergistically treated with ozone. The synergistic treatment of the sewage by the active agent and ozone can produce more hydroxyl radicals, improve the degradation efficiency of organic pollutants, enhance the oxidation capacity of ozone, and reduce the consumption of ozone; the synergistic treatment of high-valent manganese ions and anemone-like MXene composite materials with hydrogen peroxide can improve the removal efficiency of pollutants and enhance the mineralization capacity of difficult-to-degrade organic matter. Hydrogen peroxide can promote the catalytic activity of high-valent manganese ions; ozone is also a strong oxidant, which can produce a synergistic oxidation effect with high-valent manganese ions, further improving the oxidative decomposition capacity of pollutants; finally, reverse osmosis is performed to effectively remove dissolved solids, organic matter and microorganisms in the water, providing high-quality effluent.
[0033] (2) The purification method of the present invention uses a composite material containing high-valent manganese ions. By combining anemone-like MXene materials with high-valent manganese ions, the MXene material itself has a high specific surface area and good electrical conductivity. Combined with the oxidizing ability of high-valent manganese ions, it can effectively adsorb and degrade new pollutants in sewage, such as endocrine disruptors, drug residues and microplastics. The presence of high-valent manganese ions significantly enhances the oxidizing ability of the material, which can accelerate the oxidative decomposition of new pollutants and improve treatment efficiency. Thermal oxidation treatment not only improves the chemical stability of the composite material, but also may promote the recycling of materials and reduce the cost of sewage treatment. The composite nanomaterial prepared by this method is easy to handle after sewage treatment, reducing the risk of secondary pollution and being more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a comparison chart of the results of the investigation 1 of the purification method of the present invention;
[0035] Figure 2 It is a comparison chart of the results of exploration 2 of the purification method of the present invention. DETAILED DESCRIPTION
[0036] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0037] Example 1: A method for purifying new pollutants in water using a high-valent manganese ion synergistic active agent, comprising the following steps:
[0038] S1. The wastewater containing EDCs is subjected to nanofiltration treatment at a temperature of 30°C and a pressure of 20 bar, wherein the pore size of the nanofiltration membrane is 1.5 nm, to obtain filtered water;
[0039] S2. At 22°C, add the active agent to the filtered water at a solid-liquid ratio of 1 L:30 mg, and introduce ozone with a volume concentration of 3% into the filtered water at a ventilation rate of 1.5 L / min for 18 minutes.
[0040] The temperature was then raised to 50°C, and the active agent and the composite material containing high-valent manganese ions were added at a solid-liquid ratio of 1L:5mg:12.5mg. Hydrogen peroxide with a volume concentration of 6.5% was introduced into the filtered water at a ventilation rate of 0.35L / min for 8 minutes.
[0041] The temperature is then raised to 75° C., a composite material containing high-valent manganese ions is added separately at a solid-liquid ratio of 1 L:3.5 mg, and ozone with a volume concentration of 5.5% is introduced into the filtered water at a ventilation rate of 7 L / min for 8 minutes to obtain purified water; the active agent is sodium bisulfite;
[0042] S3, subjecting the purified water to reverse osmosis treatment at a temperature of 30° C. and a pressure of 20 bar, and purification is completed; the pore size of the reverse osmosis membrane is 0.0007 μm;
[0043] The preparation method of the composite material containing high-valent manganese ions is as follows:
[0044] The anemone-like MXene nanomaterial was stirred and mixed in a mixed solution at a solid-liquid ratio of 0.25 g:1 L for 4.5 hours, wherein the mixed solution was prepared by mixing a 0.25 mol / L potassium permanganate solution and a 0.8 mol / L manganese sulfate solution at a molar ratio of 1.2:1 to obtain a composite nanomaterial;
[0045] The composite nanomaterial is washed with deionized water and dried at 80° C., and then thermally oxidized at 250° C. for 35 min to obtain a composite material containing high-valent manganese ions;
[0046] The preparation method of the anemone-like MXene nanomaterial is:
[0047] The MAX phase bulk material is used as a working electrode, AgCl is used as a reference electrode, and platinum is used as a counter electrode. The working electrode, reference electrode and counter electrode are immersed in an electrolyte at a voltage of 18 V for electrochemical stripping for 5 hours, and then centrifuged at 450 rpm, washed with deionized water at 25°C, and dried at 80°C to obtain MXene nanorods; wherein the electrolyte is a mixed solution of acetone and lithium perchlorate, and the concentration of lithium perchlorate in the mixed solution is 0.15 mol / L; the aspect ratio of the MXene nanorods is 7.5; the MAX phase material is Ti3SiC2;
[0048] A MAX phase precursor powder with a particle size of 540 to 570 nm is added to deionized water to form a suspension, and the suspension is transferred to a hydrothermal reactor, heated at 150°C for 10 hours, and then centrifuged at 450 rpm, washed in deionized water at 25°C, and dried at 80°C to obtain MXene nanowires; the aspect ratio of the MXene nanowires is 22.5, and the MAX phase precursor powder is Ti3AlC2;
[0049] The prepared MXene nanorods and MXene nanowires were mixed and dissolved in a dimethyl sulfoxide solution at a mass ratio of 1:8. After mixing for 3.5 hours, they were centrifuged at 450 rpm, washed with deionized water at 25°C, and dried at 80°C to obtain anemone-like MXene nanomaterials.
[0050] Example 2: This example is different from Example 1 in that the wastewater is subjected to nanofiltration treatment at a temperature of 25°C and a pressure of 15 bar, and the pore size of the nanofiltration membrane is 1 nm.
[0051] Example 3: This example is different from Example 1 in that the sewage is subjected to nanofiltration treatment at a temperature of 35°C and a pressure of 25 bar, and the pore size of the nanofiltration membrane is 2 nm.
[0052] Example 4: This example is different from Example 1 in that, at 20°C, an active agent is added to the filtered water at a solid-liquid ratio of 1 L:20 mg.
[0053] Example 5: This example is different from Example 1 in that, at 25°C, an active agent is added to the filtered water at a solid-liquid ratio of 1 L:40 mg.
[0054] Example 6: This example differs from Example 1 in that ozone with a volume concentration of 2.5% is introduced into the filtered water at an aeration rate of 1 L / min for 15 minutes.
[0055] Example 7: This example differs from Example 1 in that ozone with a volume concentration of 3.5% is introduced into the filtered water at a ventilation rate of 2 L / min for 20 min.
[0056] Example 8: This example is different from Example 1 in that the temperature is raised to 40°C, and the active agent and the composite material containing high-valent manganese ions are added in a solid-liquid ratio of 1L:5mg:10mg.
[0057] Example 9: This example is different from Example 1 in that the temperature is raised to 60°C, and the active agent and the composite material containing high-valent manganese ions are added in a solid-liquid ratio of 1L:5mg:15mg.
[0058] Example 10: This example differs from Example 1 in that hydrogen peroxide having a volume concentration of 5% is introduced into the filtered water at an aeration rate of 0.2 L / min for 5 minutes.
[0059] Example 11: This example is different from Example 1 in that hydrogen peroxide with a volume concentration of 8% is introduced into the filtered water at a ventilation rate of 0.5 L / min for 10 minutes.
[0060] Example 12: This example is different from Example 1 in that the temperature is raised to 70°C, and a composite material containing high-valent manganese ions is added separately at a solid-liquid ratio of 1L:2mg.
[0061] Example 13: This example is different from Example 1 in that the temperature is raised to 80°C, and a composite material containing high-valent manganese ions is added separately at a solid-liquid ratio of 1L:5mg.
[0062] Example 14: This example differs from Example 1 in that ozone with a volume concentration of 5% is introduced into the filtered water at an aeration rate of 6 L / min for 5 minutes.
[0063] Example 15: This example differs from Example 1 in that ozone with a volume concentration of 6% is introduced into the filtered water at an aeration rate of 8 L / min for 10 min.
[0064] Example 16: This example is different from Example 1 in that the purified water is subjected to reverse osmosis treatment at a temperature of 25°C and a pressure of 15 bar to complete the purification; the pore size of the reverse osmosis membrane is 0.0005 μm.
[0065] Example 17: This example is different from Example 1 in that the purified water is subjected to reverse osmosis treatment at a temperature of 35°C and a pressure of 25 bar to complete the purification; the pore size of the reverse osmosis membrane is 0.0008 μm.
[0066] Example 18: This example is different from Example 1 in that the anemone-like MXene nanomaterial is stirred and mixed in a mixed solution at a solid-liquid ratio of 0.2 g:1 L for 4 hours.
[0067] Example 19: This example is different from Example 1 in that the anemone-like MXene nanomaterial is stirred and mixed in a mixed solution at a solid-liquid ratio of 0.3 g:1 L for 5 hours.
[0068] Example 20: This example is different from Example 1 in that the mixed solution is formed by mixing 0.2 mol / L potassium permanganate solution and 0.9 mol / L manganese sulfate solution in a molar ratio of 1:1.
[0069] Example 21: This example is different from Example 1 in that the mixed solution is prepared by mixing 0.3 mol / L potassium permanganate solution and 0.7 mol / L manganese sulfate solution in a molar ratio of 1.5:1.
[0070] Example 22: This example is different from Example 1 in that, after the composite nanomaterial is washed and dried, it is thermally oxidized at 200°C for 30 minutes.
[0071] Example 23: This example is different from Example 1 in that, after the composite nanomaterial is washed and dried, it is thermally oxidized at 300°C for 40 minutes.
[0072] Example 24: This example differs from Example 1 in that the voltage is 5 V, the electrochemical stripping is performed for 4 h, and the concentration of lithium perchlorate in the mixed solution is 0.1 mol / L.
[0073] Example 25: This example differs from Example 1 in that the voltage is 30 V, the electrochemical stripping is performed for 6 h, and the concentration of lithium perchlorate in the mixed solution is 0.2 mol / L.
[0074] Example 26: This example is different from Example 1 in that MAX phase precursor powder with a particle size of 500-540 nm is added to deionized water to form a suspension, and the suspension is transferred to a hydrothermal reactor with a heating temperature of 140°C and a heating time of 8 hours.
[0075] Example 27: This example differs from Example 1 in that MAX phase precursor powder with a particle size of 570 to 600 nm is added to deionized water to form a suspension, and the suspension is transferred to a hydrothermal reactor with a heating temperature of 160°C and a heating time of 12 h.
[0076] Example 28: This example is different from Example 1 in that the prepared MXene nanorods and MXene nanowires are mixed and dissolved in a dimethyl sulfoxide solution in a mass ratio of 1:5 and mixed for 3 hours.
[0077] Example 29: This example is different from Example 1 in that the prepared MXene nanorods and MXene nanowires are mixed and dissolved in a dimethyl sulfoxide solution in a mass ratio of 1:10 and mixed for 4 hours.
[0078] Example 30: This example is different from Example 1 in that the aspect ratio of the MXene nanorods is 6, and the aspect ratio of the MXene nanowires is 25.
[0079] Example 31: This example is different from Example 1 in that the aspect ratio of the MXene nanorods is 9, and the aspect ratio of the MXene nanowires is 20.
[0080] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0081] First, the initial concentration of the new pollutant (environmental endocrine disruptor bisphenol A) in the sewage is detected, and then after purification by this method, the purification concentration of the new pollutant in the purified water is tested, and (initial concentration-purification concentration) / initial concentration is used as the new pollutant degradation rate / % of this purification method.
[0082] 1. Explore the influence of parameters in each purification step on the degradation rate.
[0083] The difference between Control Example 1 and Example 1 is that hydrogen peroxide and ozone are not introduced during the treatment;
[0084] The difference between Control Example 2 and Example 1 is that no active agent is added separately;
[0085] The difference between Comparative Example 3 and Example 1 is that the composite material containing high-valent manganese ions is not added separately;
[0086] from Figure 1 The results show that the control example 1 lacks the reduction and oxidation of hydrogen peroxide and ozone, the control example 2 lacks the auxiliary effect of the active agent at low temperature, and the control example 3 lacks the purification effect of the composite material containing high-valent manganese ions at high temperature. Compared with the examples 1 to 17, the degradation rates are significantly reduced.
[0087] By comparing Examples 1 to 17, it can be seen that the parameters of nanofiltration are too small or too large, the parameters of the active agent added alone are too small or too large, the parameters of the ozone synergistic active agent treatment are too small or too large, the parameters of the active agent synergistic composite material containing high-valent manganese ions are too small, the parameters of the hydrogen peroxide entry are too small or too large, the parameters of the composite material containing high-valent manganese ions added alone are too small, the parameters of the ozone synergistic composite material containing high-valent manganese ions are too small or too large, and the reverse osmosis parameters are too small, which will reduce the degradation rate of new pollutants; among them, the degradation rates of Examples 9, 13 and 17 are the same or improved compared with those of Example 1, but the improvement is too small, so from an economic point of view, the parameter effect of Example 1 is relatively better.
[0088] 2. Investigate the effects of various preparation parameters of composite materials containing high-valent manganese ions on the degradation rate.
[0089] The difference between Control Example 4 and Example 1 is that the MXene nanomaterial is in the form of individual nanorods;
[0090] from Figure 2 The results show that the MXene nanomaterial in Control Example 4 lacks the anemone morphology, that is, lacks nanowires, so the degree of binding with high-valent manganese ions is reduced at the same dosage, thereby reducing the content of high-valent manganese ions carried, and therefore the degradation rates are all reduced compared to Examples 18 to 31;
[0091] By comparing Examples 1 and 18 to 31, it can be seen that the degradation rate of pollutants will be reduced if the proportion of anemone-like MXene nanomaterials is too small or too large, the proportion of potassium permanganate solution in the mixed solution is too small or too large, the thermal oxidation parameters are too small or too large, the electrochemical stripping parameters are too small or too large, the hydrothermal reaction parameters are too small or too large, the proportion of nanorods is too small or too large, and the difference in the aspect ratio of nanorods and nanowires is too small or too large. Therefore, in comprehensive comparison, the parameter effect of Example 1 is relatively better.
Claims
1. A method for preparing a composite material containing high-valent manganese ions, characterized in that: The following steps are involved: The anemone-like MXene nanomaterial is stirred and mixed in a mixed solution at a solid-liquid ratio of 0.2-0.3 g:1 L for 4-5 hours, wherein the mixed solution is prepared by mixing a 0.2-0.3 mol / L potassium permanganate solution and a 0.7-0.9 mol / L manganese sulfate solution at a molar ratio of 1-1.5:1 to obtain a composite nanomaterial; After washing and drying the composite nanomaterial, thermally oxidizing it at 200-300° C. for 30-40 min to obtain a composite material containing high-valent manganese ions; The preparation method of the anemone-like MXene nanomaterial is: Using MAX phase bulk material as a working electrode, AgCl as a reference electrode, and platinum as a counter electrode, the working electrode, reference electrode, and counter electrode are immersed in an electrolyte at a voltage of 5 to 30 V, and electrochemical stripping is performed for 4 to 6 hours, followed by centrifugal washing and drying to obtain MXene nanorods; wherein the electrolyte is a mixed solution of acetone and lithium perchlorate, and the concentration of lithium perchlorate in the mixed solution is 0.1 to 0.2 mol / L; The MAX phase precursor powder with a particle size of 500-600 nm was added to deionized water to form a suspension, and the suspension was transferred to a hydrothermal reactor, heated at 140-160°C for 8-12 hours, and then centrifuged, washed and dried to obtain MXene nanowires; The prepared MXene nanorods and MXene nanowires were mixed and dissolved in a dimethyl sulfoxide solution at a mass ratio of 1:5-10, mixed for 3-4 hours, and then centrifuged, washed, and dried to obtain anemone-like MXene nanomaterials; The MAX phase bulk material is Ti3SiC2, and the MAX phase precursor powder is Ti3AlC2.
2. The method for preparing a composite material containing high-valent manganese ions according to claim 1, characterized in that: The aspect ratio of the MXene nanorods is 6-9, and the aspect ratio of the MXene nanowires is 20-25.
3. A method for purifying new pollutants in water using high-valent manganese ions in collaboration with an active agent, characterized in that: The following steps are involved: S1. Perform nanofiltration treatment on the sewage at a temperature of 25-35°C and a pressure of 15-25 bar to obtain filtered water; S2. At 20-25°C, add the active agent to the filtered water at a solid-liquid ratio of 1L:20-40mg, and introduce ozone with a volume concentration of 2.5-3.5% into the filtered water at a ventilation rate of 1-2L / min for 15-20min. The temperature is then raised to 40-60° C., an active agent and the composite material containing high-valent manganese ions as claimed in claim 1 are added at a solid-liquid ratio of 1 L: 5 mg: 10-15 mg, and hydrogen peroxide with a volume concentration of 5-8% is introduced into the filtered water at a ventilation rate of 0.2-0.5 L / min for 5-10 minutes. The temperature is then raised to 70-80° C., the composite material containing high-valent manganese ions as claimed in claim 1 is added separately at a solid-liquid ratio of 1 L:2-5 mg, and ozone with a volume concentration of 5-6% is introduced into the filtered water at a ventilation rate of 6-8 L / min for 5-10 minutes to obtain purified water; S3. The purified water is subjected to reverse osmosis treatment at a temperature of 25-35° C. and a pressure of 15-25 bar to complete the purification.
4. The method for purifying new pollutants in water using a high-valent manganese ion synergistic active agent as claimed in claim 3, characterized in that: In step S1, the pore size of the membrane used in the nanofiltration treatment is 1-2 nm; in step S3, the pore size of the membrane used in the reverse osmosis treatment is 0.0005-0.0008 μm.
5. The method for purifying new pollutants in water using a high-valent manganese ion synergistic active agent as claimed in claim 3, characterized in that: The active agent is sodium bisulfite.
6. The method for purifying new pollutants in water using a high-valent manganese ion synergistic active agent as claimed in claim 3, characterized in that: The temperature of the nanofiltration treatment is 25-35° C. and the pressure is 15-25 bar.
7. The method for purifying new pollutants in water using a high-valent manganese ion synergistic active agent as claimed in claim 3, characterized in that: The new pollutants are one or more of EDCs, PPCPs, NMs, PFCs, BFRs, and ARmg.
Citation Information
Patent Citations
Ozonization water treatment method using manganese dioxide one-dimensional nano material as catalyst
CN101891297A
Preparation method of two-dimensional adsorbent titanium carbide for effectively treating potassium permanganate solution
CN104549149A